2020
DOI: 10.1097/mcg.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

Digital Single-operator Cholangioscopy (DSOC) Improves Interobserver Agreement (IOA) and Accuracy for Evaluation of Indeterminate Biliary Strictures

Abstract: Background: Visual characteristics seen during digital single-operator cholangioscopy (DSOC) have not been validated. The aim of this 2-phase study was to define terminology by consensus for the visual diagnosis of biliary lesions to develop a model for optimization of the diagnostic performance of DSOC. Materials and Methods:In phase 1 (criteria identification), video-cholangioscopy clips were reviewed by 12 expert biliary endoscopists, who were blinded to the final diagnosis. Visual criteria were consolidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…According to this survey, the evaluation of biliary strictures was one of the main indications for cholangioscopy. Previous studies have shown very good results regarding the diagnostic accuracy of visual characteristics for determining the etiology of strictures, but considerable interobserver variation exists among endoscopists 4 5 . Morphological features of malignant and inflammatory disease may overlap significantly and not be exclusive or clearly discriminative, even for experienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…According to this survey, the evaluation of biliary strictures was one of the main indications for cholangioscopy. Previous studies have shown very good results regarding the diagnostic accuracy of visual characteristics for determining the etiology of strictures, but considerable interobserver variation exists among endoscopists 4 5 . Morphological features of malignant and inflammatory disease may overlap significantly and not be exclusive or clearly discriminative, even for experienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Monaco classification has been reported to address this problem. In this study [31], the visual standards were merged into eight categories: stricture, lesion, mucosal features, papillary projections, ulceration, abnormal vessels, scarring, and pronounced pit pattern. The IOA and diagnostic accuracy of DSOC significantly improved with this classification when compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was pathologically correlated with the subepithelial spreading of fibrotic tumor which resulted in greater difficulty in acquiring diagnostic tissue when compared with the other criteria (37). Notably, the subsequent validation studies demonstrated that tumor vessels, papillary projection, nodules, and infiltrative lesions had fair to moderate inter-observer agreement with Kappa value of 0.12-0.26, 0.43-0.54, 0.26, and 0.34, respectively (Table 5) (39,40). Nevertheless, the consensus panelists agreed these four criteria are important and should be assessed when visual impression is required for biliary malignancy diagnosis.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%